Collected Works of C. G. Jung, Volume 11 : Psychology and Religion: West and East - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 1973)
Sixteen studies in religious phenomena, including Psychology and Religion and Answer to Job.